Mathematical Communication Ability in Problem Based Learning with STEAM Approach Viewed from Learning Styles - Prasetiawan, Aditya Hendra; Mastur, Zaenuri; Waluya, Stevanus Budi (Universitas Muria Kudus, 2023)
The purpose of this research is to analyze the quality of PBL learning with STEAM approach to mathematical communication abilities of 8th grade students at SMPN 1 Tonjong and to analyze mathematical communication abilities of 8th grade students at SMPN 1 Tonjong in PBL learning with STEAM approach viewed from learning style. The research method used is mix methods. The research design used is a sequential explanatory design. Sample selection used a cluster random sampling technique. The population in this study were 8th grade students at SMPN 1 Tonjong while the samples were 28 students of class 8A as the experimental class and 28 students of class 8C as the control class. Data collection methods include observation, test, interviews and documentation. Data analysis includes normality test, homogeneity test, classical completeness test, average difference test and proportion difference test. The results of this research show that mathematics learning with PBL model using a STEAM approach is on high quality for mathematical communication ability because fulfill valid, practical and effective criteria. The results of the qualitative analysis show that each learning style fulfill different indicators of mathematical communication ability. criteria. It is means that differences in students learning styles influence their mathematical communication ability.